Analisis Yuridis Izin Pencipta Sebagai Syarat Untuk Melaksanakan Hak Ekonomi Pemegang Hak Cipta - Muchammad Dwi Nurwachidiansyah; Icha Cahyaning Fitri (Empat Sembilan Publisher, 2025)
The diversity of Indonesian art and culture as part of intellectual wealth, holds strategic value not only culturally but also economically, thus requiring effective legal protection. In the copyright regime, Article 9 paragraph (2) of Law Number 28 of 2014 on Copyright states that the exercise of economic rights must be based on the authorization of the creator or copyright holder. However, the provisions of Article 10 paragraph (1) of Government Regulation Number 56 of 2021, which regulates royalty payments through the National Collective Management Institution, have led to multiple interpretations regarding whether royalty payments can replace the creator's authorization. This study aims to understand and analyze the creator's authorization as an absolute requirement in the exercise of economic rights, as well as to examine the legal consequences of utilizing works without the creator's permission. The research method used is normative juridical with an approach based on legislation and conceptual analysis. The research results indicate that the obligation of the creator's permission is conditionally mandatory, with limited exceptions through the blanket license mechanism as regulated in Article 23 paragraph (5) and Article 87 paragraph (4) of the Copyright Law, which only applies to performing rights. Meanwhile, mechanical rights and synchronization rights still require a direct license from the creator. The absence of the creator's permission in commercial use results in the loss of legal basis for exercising economic rights and causes legal liability in the form of civil, criminal, and administrative sanctions.